Correlates of patient satisfaction with pain management at the Ho Teaching Hospital in Ghana: A cross-sectional study - Donatus Wewura Adongo; Charles Kwaku Benneh; Hilda Amekyeh; David Adedia; Augustine Tandoh; Isaac Junior Armah; James Kwaku Agyen; Eric Okyere; Eric Woode (Scientific African, 2023)
Pain is a symptom that many people who visit the hospital with various illnesses experience. Inadequate pain management has been regularly shown to have a negative impact on patients' health and reduce patient satisfaction. Patients' satisfaction with pain management is therefore important. The aim of this study was therefore to assess patients’ satisfaction and experience with pain management at the Ho Teaching Hospital, Volta Region, Ghana. The study was a prospective cross-sectional investigation and was carried out among 196 adult patients (older than 18 years) at the emergency, medical, and surgical wards. Data was collected using the 2010 version of the patient outcome and satisfaction survey questionnaire developed by the American Pain Society. Descriptive and inferential statistical analysis were employed in analysing the data obtained from the respondents. p-value less than 0.05 was considered as statistically significant.The results revealed that 96% of the respondents were satisfied with their pain management. Expectations for pain treatment (r = 0.221, p-value=0.002), percentage of pain relief in first 48 h (r = 0.439, p-value<0.001) and how helpful the information was (r = 0.158, p-value=0.027) were positively correlated with satisfaction with pain treatment. In addition, the median satisfaction with pain treatment was higher for those with knowledge on pain medication (p-value=0.043), and patients who were allowed to participate in decision-making indicated a higher level of satisfaction.The majority of patients (95% with acute pain and 100% with chronic pain) were satisfied with their pain management. Aside the effective use of analgesics, it was found that patient satisfaction can also be enhanced by good patient-provider relationships, providing patients with helpful information about their pain treatment, and allowing patients to participate in decisions about their pain management. This research is the first to provide such information for pain management in the Volta Region of Ghana.